Best Practices for Teaming and Collaboration in the Interconnected Systems Framework. Issue 4 (2nd October 2017) - Splett, Joni W.; Perales, Kelly; Halliday-Boykins, Colleen A.; Gilchrest, Callie E.; Gibson, Nicole; Weist, Mark D.
ABSTRACT: The Interconnected Systems Framework (ISF) blends school mental health practices, systems, and resources into all levels of a multitiered system of supports (e.g., positive behavior interventions and supports). The ISF aims to improve mental health and school performance for all students by emphasizing effective school-wide promotion and prevention; early identification; and social-emotional, behavioral, and mental health intervention. Teaming is 1 of 3 foundational components of quality ISF implementation at school, district, and state levels. After introducing the ISF, the authors highlight the core implementation components (i.e., teaming, data-based decision making, and evidence-based practices) and then elaborate on characteristics of well-functioning ISF teams. The authors provide a case example to illustrate each characteristic and review 5 measures teams may consider using to evaluate their functioning and SF implementation.